2011
DOI: 10.2147/dmso.s24221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan fasting on metabolic markers, body composition, and dietary intake in Emiratis of Ajman (UAE) with metabolic syndrome

Abstract: Background/aimThe aim of the study was to evaluate the effect of Ramadan fasting on metabolic markers, body composition and dietary intake in native Emiratis of Ajman, UAE with the metabolic syndrome (MS).Design19 patients (14 Female, 5 Male) aged 37.1 ± 12.5 years, were encouraged healthy lifestyle changes during fasting and data was collected 1 week before and in the fourth week of Ramadan.ResultsNo patients experienced complications or increased symptoms of hypoglycemia during Ramadan. Total energy consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
88
3
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 29 publications
19
88
3
3
Order By: Relevance
“…Our results showed that subjects belong to United Arab Emirates showed a significant loss in weight, but no significant improvement in total cholesterol and HDL level. These results are in accordance with previous research done before in UAE by Sadiya and her group, where follow-up of 19 native Emiratis with metabolic syndrome showed significant decrease in body weight and waist circumference, slight increase in fasting glucose and HBA1c but no change in lipid parameters after Ramadan fasting [7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that subjects belong to United Arab Emirates showed a significant loss in weight, but no significant improvement in total cholesterol and HDL level. These results are in accordance with previous research done before in UAE by Sadiya and her group, where follow-up of 19 native Emiratis with metabolic syndrome showed significant decrease in body weight and waist circumference, slight increase in fasting glucose and HBA1c but no change in lipid parameters after Ramadan fasting [7].…”
Section: Discussionsupporting
confidence: 93%
“…The Emirati participants had their weight reduced from the region. The weight and weight circumference has dropped significantly during Ramadan (103.9 ± 29.8 vs 102.1 ± 29.0 kg, P=0.001 and waist circumference 123 ± 14 vs 119 ± 17 cm, P=0.001), in this study there was a non-statistically significant increase in fasting blood glucose and HbA1c [7]. Jamil-ur-Rehman et al studied 24 healthy males who fasted the month of Ramadan, and assessed their metabolic profiles before and after Ramadan.…”
Section: Resultscontrasting
confidence: 55%
“…In the study of Sadiya et al the levels of FFM, FM, FM% and FFM% had a slow drop, almost one kg and one percent, respectively, between the first week and fourth weeks of Ramadan (15). In a study undertaken by Mirzaei et al significant changes in body composition and also about two kg decrease in FFM and FM were reported, among the athletes (29).…”
Section: Changes Of Fat Mass and Fat Free Mass During Fastingmentioning
confidence: 99%
“…Most studies indicate that weight and BMI decrease noticeably during Ramadan. Despite finding insignificant changes in the total energy intake, Sadyia et al detected a significant reduction in total weight and BMI after 4 weeks of Ramadan (15). Another survey showed a downward trend in second week of Ramadan in comparison to baseline, however, it increased significantly after Ramadan (8).…”
Section: Body Weight and Body Mass Indexmentioning
confidence: 99%
“…Selain itu melalui puasa beberapa orang justru aktivitas fisiknya akan meningkat hal ini dikarenakan efek berdoa yang dilakukan lebih banyak disaat melakukan puasa. 58 Dalam perspektif agama Islam, ibadah puasa merupakan suatu syariat yang diwajibkan bagi setiap muslim. Seperti yang terdapat dalam QS.…”
unclassified